Early detection and management of extracranial arteriopathy reduces the incidence of silent cerebral infarcts in sickle cell anemia: a long-term prospective cohort study - Francoise Bernaudin; Cecile Arnaud; Annie Kamdem; Jenny Youn; Manuela Vasile; Isabelle Hau; Fouad Madhi; Aline Malterre; Celine Delestrain; Ralph Epaud; Camille Jung; Suzanne Verlhac (Haematologica)
Previous reports about the Creteil newborn-cohort (1988/Apr-2007) showed that the risk of silent cerebral infarcts (SCI) remained high (37.1%) by age 14 in children with sickle cell anemia (SCA) and intracranial time-averaged mean maximum velocity (TAMMV)≥200cm/s despite chronictransfusion. Systematic assessment of extracranial internal carotid artery (eICA) since June-2011 revealed that SCI-risk is associated with chronic or acute anemia and eICA-stenosis. Based on these results, SCA-children with eICA-TAMMV≥200cm/s or eICA-stenosis were placed on chronictransfusion and considered for allogeneic stem-cell transplantation (alloSCT). SCA-children with 160-199cm/s eICA-TAMMV were maintained on hydroxyurea. We hypothesized that detection/management of eICA-arteriopathy and wider use of hydroxyurea could reduce SCI-incidence.